2017
DOI: 10.1021/acsmedchemlett.6b00464
|View full text |Cite|
|
Sign up to set email alerts
|

Structure Based Design of Non-Natural Peptidic Macrocyclic Mcl-1 Inhibitors

Abstract: Mcl-1 is a pro-apoptotic BH3 protein family member similar to Bcl-2 and Bcl-xL. Overexpression of Mcl-1 is often seen in various tumors and allows cancer cells to evade apoptosis. Here we report the discovery and optimization of a series of non-natural peptide Mcl-1 inhibitors. Screening of DNA-encoded libraries resulted in hit compound , a 1.5 μM Mcl-1 inhibitor. A subsequent crystal structure demonstrated that compound bound to Mcl-1 in a β-turn conformation, such that the two ends of the peptide were close … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 20 publications
0
54
0
Order By: Relevance
“…These findings may have clinical relevance in that certain TNBCs overexpressing MCL-1 and BCL2A1 could exhibit resistance to MCL-1 inhibitors that are under development. 38 40 In this context, we found that BT-20/ABT-737R cells, which overexpress MCL-1 and BCL2A1, were sensitive to targeting MCL-1 with MS1/NPs. By contrast, MDA-MB-468/ABT-737R cells, which also overexpress MCL-1 and BCL2A1, were resistant to targeting MCL-1.…”
Section: Discussionmentioning
confidence: 95%
“…These findings may have clinical relevance in that certain TNBCs overexpressing MCL-1 and BCL2A1 could exhibit resistance to MCL-1 inhibitors that are under development. 38 40 In this context, we found that BT-20/ABT-737R cells, which overexpress MCL-1 and BCL2A1, were sensitive to targeting MCL-1 with MS1/NPs. By contrast, MDA-MB-468/ABT-737R cells, which also overexpress MCL-1 and BCL2A1, were resistant to targeting MCL-1.…”
Section: Discussionmentioning
confidence: 95%
“…These compounds, however, show poor aqueous solubility and cell permeability and therefore will require further optimization (Rosenthal et al, 2013) In addition to peptidomemetics, macrocyles have shown promise in providing a distinct solution to the problem effectively competing with macromolecular-macromolecular interactions. Johannes and colleagues (Johannes et al, 2017) recently employed a DNA-encoded library of non-natural peptides in a screening campaign against Mcl-1, a pro-apoptotic protein. Importantly, structures of the initial hits allowed the researchers to link the terminal ends of the ligand, to form a macrocylic analog, which led to a binding enhancement of more than an order of magnitude.…”
Section: Challenges In Developing Inhibitors/modulators Of Dna Repairmentioning
confidence: 99%
“…A range of recent structure-based drug discovery case studies demonstrate the power of nuclear magnetic resonance (NMR) conformational analysis to elucidate SAR trends with respect to conformational preferences of the free ligand [4][5][6][7][8][9][10][11][12][13][14]. In the majority of cases, knowledge of the free ligand conformational preference clearly aided structure-based design.…”
mentioning
confidence: 99%
“…If we combine this information with target affinity, we can often rationalize SAR which is independent of any specific ligand-protein interaction. A recent example was described by Johannes et al [4] in their design of macrocyclic inhibitors of MCL1. In this case they used knowledge of anomalous proton NMR chemical shifts caused by anisotropic shielding to understand that their most potent macrocycle, containing a methylated amide, had a conformational lock which biased it towards adopting the bioactive conformation in solution.…”
mentioning
confidence: 99%